2005
DOI: 10.1111/j.1476-5810.2005.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Curative‐intent radiation therapy as a treatment modality for appendicular and axial osteosarcoma: a preliminary retrospective evaluation of 14 dogs with the disease

Abstract: Canine osteosarcoma is a common bone malignancy associated with aggressive local disease and rapid metastasis. Current local therapeutic modalities do not provide curative-intent options for dogs with significant orthopaedic or neurologic disease, dogs which are denied amputation or dogs with non-resectable lesions. The goals of this retrospective study included the evaluation of local control, survival, and time to the development of metastases in 14 dogs treated with curative-intent radiation therapy and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 11 publications
3
56
0
Order By: Relevance
“…Previous studies have suggested that high LET is effective to cells with normal cellular DNA repair capacity (36,37). Furthermore, in a recent investigation, a variable response to radiation was detected clinically in dogs affected by OSA (38). Although it was beyond the scope of the present study, investigation into the DNA repair deficiencies of the radiosensitive OSA cell line may provide an insight into whether tumor cell radiosensitivity can be used as an indicator of clinical response to radiation therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have suggested that high LET is effective to cells with normal cellular DNA repair capacity (36,37). Furthermore, in a recent investigation, a variable response to radiation was detected clinically in dogs affected by OSA (38). Although it was beyond the scope of the present study, investigation into the DNA repair deficiencies of the radiosensitive OSA cell line may provide an insight into whether tumor cell radiosensitivity can be used as an indicator of clinical response to radiation therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Over the years, advances in disease management, including ‘limb-sparing’ surgical and radioablative methods used only to selectively eradicate tumors located in the distal radius, ulna and tibia have been described [18,19]. Adjuvant therapy, such as multimodal chemotherapy regimes, treatment with bisphosphonates or immune modulators and palliative radiation, can also be provided and are reported to improve clinical or survival outcome [20-23]. Combination of therapy modalities and drugs may contribute significantly to survival statistics but randomized, double-blinded studies have not been performed routinely.…”
Section: Introductionmentioning
confidence: 99%
“…However, complications associated with these procedures are common, including infection (in up to 78% of cases), tumor recurrence (rates as high as 24%), and construct failure (in up to 40% of cases). Limb salvage by curative intent radiation therapy for local tumor control has been described using full‐course fractionated therapy, intraoperative extracorporeal radiation therapy, and stereotactic radiosurgery, but resulted in pathologic fractures in up to 60% of cases . Dogs undergoing palliative medical care for appendicular OSA have recently been reported to sustain pathologic fractures in 38% of cases, with a median time from diagnosis to euthanasia or death of 111 days .…”
Section: Introductionmentioning
confidence: 99%